2020
DOI: 10.1088/1475-7516/2020/01/038
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the accuracy of the Alcock-Paczyński scaling of baryon acoustic oscillation measurements

Abstract: We investigate -in a generic setting -the regime of applicability of the Alcock-Paczyński (AP) scaling conventionally applied to test different cosmological models, given a fiducial measurement of the baryon acoustic oscillation (BAO) characteristic scale in the galaxy 2-point correlation function. We quantify the error in conventional AP scaling methods, for which our ignorance about the true cosmology is parameterised in terms of two constant AP scaling parameters. We propose a new, and as it turns out, impr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
(219 reference statements)
0
10
0
Order By: Relevance
“…First, the use of the Alcock-Paczynski scaling parameters [47] to extract the BAO frequency from the three-dimensional galaxy distribution is accurate if the Universe has a local Friedman-Robertson-Walker geometry (see, e.g., Refs. [48][49][50]), which clearly holds true in the EDE model. Second, the BAO frequency can be extracted from the postreconstruction position space correlation function (or the power spectrum) by fitting the BAO peak (or Fourier-space BAO wiggles) with a simple Gaussian (or harmonic) template, which does not rely on any cosmology-specific information.…”
Section: The Early Dark Energy Proposalmentioning
confidence: 60%
“…First, the use of the Alcock-Paczynski scaling parameters [47] to extract the BAO frequency from the three-dimensional galaxy distribution is accurate if the Universe has a local Friedman-Robertson-Walker geometry (see, e.g., Refs. [48][49][50]), which clearly holds true in the EDE model. Second, the BAO frequency can be extracted from the postreconstruction position space correlation function (or the power spectrum) by fitting the BAO peak (or Fourier-space BAO wiggles) with a simple Gaussian (or harmonic) template, which does not rely on any cosmology-specific information.…”
Section: The Early Dark Energy Proposalmentioning
confidence: 60%
“…However, it is more convenient to switch to the geodesic distances between galaxies and consider the "deprojected" three-dimensional power spectrum instead of the two-dimensional angular power spectrum [76]. In practice, the change of coordinates is realized by means of the so-called Alcock-Paczynski scaling parameters that are based on some trial fiducial cosmology [77][78][79][80]. Importantly, if the trial cosmology is different from the correct one, the reconstructed 3D power spectrum appears distorted compared to the true one [81].…”
Section: F Alcock-paczynski Effectmentioning
confidence: 99%
“…Refs. [426,427] have shown that the standard underlying cosmology assumptions are accurate as long as the Universe can be locally described with the isotropic and homogeneous FLRW metric. This is certainly true for most of the cosmological models that are aimed to fit all available cosmological data.…”
Section: B Bao and The Sound Horizon Problemmentioning
confidence: 99%